Wonderland - 911; Virgin Records (United Kingdom : Virgin Records, 1999)
Contains three tracks taken from the album The Greatest Hits And A Little Bit More.
CD 1 : Wonderland / (4:14) -- Re-United / (3:49) -- I Wanna Get Next To You / (3:44).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English